2006
DOI: 10.1111/j.1525-1438.2006.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival in ovarian cancer in Wales: prior to introduction of all Wales guidelines

Abstract: The objective of the study was to review referral practice, overall management, and survival in women with suspected ovarian cancer in Wales. This study was done prior to introduction of cancer management guidelines in the region. A confidential study questionnaire was sent to 20 participating hospitals. Data on 287 consecutive women with suspected ovarian cancer were collected, of which 250 women underwent primary laparotomy. Information was obtained on referral pattern, preoperative investigations, place of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 24 publications
2
34
0
Order By: Relevance
“…6,9,11,18,20 Similar to others, we found that women with clear cell, endrometrioid and mucinous type had the poorest survival, possibly reflecting aggressive tumor biology or less sensitivity to routinely used chemotherapy. However, Benvito et 23 and Shysasree et al 28 were not found of survival differences between subtypes and survival. Akhtar-Danesh et al 22 reported that the worst survival observed for serous tumors.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…6,9,11,18,20 Similar to others, we found that women with clear cell, endrometrioid and mucinous type had the poorest survival, possibly reflecting aggressive tumor biology or less sensitivity to routinely used chemotherapy. However, Benvito et 23 and Shysasree et al 28 were not found of survival differences between subtypes and survival. Akhtar-Danesh et al 22 reported that the worst survival observed for serous tumors.…”
Section: Discussionmentioning
confidence: 95%
“…Consistent with other work, we also revealed that high stage had significantly effect on OS (p< 0.05). In contrast, Shylasree et al 28 analyzed the outcomes of 250 women with OC and there were no significant differences regarding stage between OS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Population based data on the number of advanced ovarian cancer patients operated by a gynaecological oncologist are available in the literature for Sweden [22], Finland [23], Switzerland [24], United Kingdom [25][26][27], Denmark [28], the Netherlands [29] and Norway [30]. Data are summarised in Table 1.…”
Section: Specialisation Of Surgeonsmentioning
confidence: 99%